2015
DOI: 10.3201/eid2111.150497
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Effects of Respiratory Syncytial Virus Infection during Pregnancy

Abstract: Clarifying these effects could show potential benefits of RSV vaccination of pregnant women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 23 publications
0
44
1
Order By: Relevance
“…There, children die in excess of 20‐fold more than in industrialized nations . Neonatal deaths (0‐28 days) are frequent, particularly early after birth . And the proportion of deaths in the post‐neonatal period (29‐364 days) is higher than in industrialized countries .…”
Section: Respiratory Diseases Are a Leading Cause Of Mortality In Youmentioning
confidence: 99%
See 2 more Smart Citations
“…There, children die in excess of 20‐fold more than in industrialized nations . Neonatal deaths (0‐28 days) are frequent, particularly early after birth . And the proportion of deaths in the post‐neonatal period (29‐364 days) is higher than in industrialized countries .…”
Section: Respiratory Diseases Are a Leading Cause Of Mortality In Youmentioning
confidence: 99%
“…Neonatal deaths (0‐28 days) are frequent, particularly early after birth . And the proportion of deaths in the post‐neonatal period (29‐364 days) is higher than in industrialized countries . Pneumonia and diarrhea are responsible for most fatalities during post‐neonatal infancy and early childhood …”
Section: Respiratory Diseases Are a Leading Cause Of Mortality In Youmentioning
confidence: 99%
See 1 more Smart Citation
“…One woman did report symptoms of LRTI during hospitalization for fever and uterine contractions and was found to have PCRconfirmed RSV several days after hospital discharge. She, like those in the case-series by Wheeler et al, reported co-morbidities that may have put her at risk for a more serious illness [13].…”
Section: Discussionmentioning
confidence: 69%
“…Maternal RSV infection has not been well defined, both in regards to rate of infection and consequences of infection. A case-series study was the first to describe severe RSV infection during pregnancy: two of the three cases were hospitalized and required mechanical ventilation [13]. In addition, several large prospective maternal cohort studies of influenza-like illness (ILI) evaluated during influenza vaccine trials have described maternal RSV infection incidences of 3.9/1000 person-years in Nepal, 5.3/1000 person-months in South Africa, and 0.3/1000 persondays in Mongolia [14][15][16].…”
Section: Introductionmentioning
confidence: 99%